Monetary policy and large crises in a financial accelerator agent-based model - Federico Giri; Luca Riccetti; Alberto Russo; Mauro Gallegati (Kiel University, FinMaP - Financial Distortions and Macroeconomic Performance, 2016)
An accommodating monetary policy followed by a sudden increase of the short term interest rate often leads to a bubble burst and to an economic slowdown. Two examples are the Great Depression of 1929 and the Great Recession of 2008. Through the implementation of an Agent Based Model with a financial accelerator mechanism we are able to study the relationship between monetary policy and large scale crisis events. The main results can be summarized as follow: a) sudden and sharp increases of the policy rate can generate recessions; b) after a crisis, returning too soon and too quickly to a normal monetary policy regime can generate a dip" recession, while c) keeping the short term interest rate anchored to the zero lower bound in the short run can successfully avoid a further slowdown.
info:eu-repo/grantAgreement/EC/FP7/612955
Keywords: E32; E44; E58; C63; 330; Monetary Policy; Large Crises; Agent Based Model; Financial Accelerator; Zero Lower Bound